Elevated pH Conditions Associated With Microcystis spp. Blooms Decrease Viability of the Cultured Diatom Fragilaria crotonensis and Natural Diatoms in Lake Erie - Zepernick, Brittany N.; Gann, Eric R.; Martin, Robbie M.; Pound, Helena L.; Krausfeldt, Lauren E.; Chaffin, Justin D.; Wilhelm, Steven W. (Frontiers in Microbiology, 2021)
Cyanobacterial Harmful Algal Blooms (CyanoHABs) commonly increase water column pH to alkaline levels ≥9.2, and to as high as 11. This elevated pH has been suggested to confer a competitive advantage to cyanobacteria such as Microcystis aeruginosa. Yet, there is limited information regarding the restrictive effects bloom-induced pH levels may impose on this cyanobacterium’s competitors. Due to the pH-dependency of biosilicification processes, diatoms (which seasonally both precede and proceed Microcystis blooms in many fresh waters) may be unable to synthesize frustules at these pH levels. We assessed the effects of pH on the ecologically relevant diatom Fragilaria crotonensis in vitro, and on a Lake Erie diatom community in situ. In vitro assays revealed F. crotonensis monocultures exhibited lower growth rates and abundances when cultivated at a starting pH of 9.2 in comparison to pH 7.7. The suppressed growth trends in F. crotonensis were exacerbated when co-cultured with M. aeruginosa at pH conditions and cell densities that simulated a cyanobacteria bloom. Estimates demonstrated a significant decrease in silica (Si) deposition at alkaline pH in both in vitro F. crotonensis cultures and in situ Lake Erie diatom assemblages, after as little as 48 h of alkaline pH-exposure. These observations indicate elevated pH negatively affected growth rate and diatom silica deposition; in total providing a competitive disadvantage for diatoms. Our observations demonstrate pH likely plays a significant role in bloom succession, creating a potential to prolong summer Microcystis blooms and constrain diatom fall resurgence.